2013
DOI: 10.1016/j.neuint.2012.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of T cell deficiency against brain injury are ischemic model-dependent in rats

Abstract: Previous studies have reported that T cell deficiency reduced infarct sizes after transient middle cerebral artery (MCA) suture occlusion in mice. However, how reperfusion and different models affect the detrimental effects of T cells have not been studied. We investigated the effects of T cell deficiency in nude rats using two stroke models and compared their infarct sizes with those in WT rats. In the distal MCA occlusion (MCAo) model, the distal MCA was permanently occluded and the bilateral common carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…There are a series of experiments that show the harmful role of T lymphocytes, among which are those performed by Gokhan [26] and his team in 2006 where they observed that lymphocytes are the primary producers of INF-and other proinlammatory cytokines, that promotes an increment in infarct size [26] and those performed by Liesz in 2011 [63], in which they observed that by eliminating lymphocytes, infarct size was reduced in animals subjected to cerebral ischemia, all of which matches with Xiong et al's results in 2013 [64], where they observed that T lymphocyte deiciency signiicantly reduces infarct volume in a transient cerebral ischemia model, but not in distal permanent occlusion, which highlights that the model and level of reperfusion used are essential and diferential to evaluate damage.…”
Section: +supporting
confidence: 61%
See 1 more Smart Citation
“…There are a series of experiments that show the harmful role of T lymphocytes, among which are those performed by Gokhan [26] and his team in 2006 where they observed that lymphocytes are the primary producers of INF-and other proinlammatory cytokines, that promotes an increment in infarct size [26] and those performed by Liesz in 2011 [63], in which they observed that by eliminating lymphocytes, infarct size was reduced in animals subjected to cerebral ischemia, all of which matches with Xiong et al's results in 2013 [64], where they observed that T lymphocyte deiciency signiicantly reduces infarct volume in a transient cerebral ischemia model, but not in distal permanent occlusion, which highlights that the model and level of reperfusion used are essential and diferential to evaluate damage.…”
Section: +supporting
confidence: 61%
“…Natural killer NK cells have a less noxious efect. T cells show an injurious efect at the experimental level through the production of IL-1 , IL-23 [38,63,64] and IL-6 at the clinical level [6 ]. Treg lymphocytes have been implicated mostly in neural tissue protection, preventing autoimmunity and inlammation through IL-10 [66].…”
Section: +mentioning
confidence: 99%
“…T cells in the ischemic brains than dMCAO. We believed that the reason caused above phenomena were mainly associated with different degrees of reperfusion [35].…”
Section: The Effects Of T Cells On Ischemic Brainmentioning
confidence: 96%
“…The absence of T cells has been shown by several groups to reduce ischemic injury, although the extent of reperfusion may be important to this effect (193). Paradoxically, poststroke immune suppression is known to render stroke patients vulnerable to infections, including pneumonia and sepsis, acting, in part, by activation of the a7 nicotinic acetylcholine receptor to inhibit neutrophil and macrophage accumulation and function (91).…”
Section: Immune Response To Strokementioning
confidence: 99%